HUBUNGAN DUKUNGAN PASANGAN DAN PEMBERIAN ASI EKSKLUSIF DI DESA TANDAN SARI KECAMATAN TAPUNG HILIR KABUPATEN KAMPAR PROVINSI RIAU - Andalia Roza; Rizky Dwi Lestari (Jurnal Keperawatan Abdurrab, 2021)
Couple’s support having a role in the success or failure of a mother to breastfeed her baby. The greater the support obtained to breastfeed,the greater the ability to survive. This research aimed to know the couple’s support with exclusive breastfeeding in Tandan sari Village Tapung hilir Sub-district Kampar Regency in Riau Province. The design of this research used a descriptive correlation study with a cross sectional approach. The population in this research were mother’s who had children aged 6 -24 month’s. the sample in this research amounted to 65 respondents. Data collection was carried out in march 2020 with the use of a questionnaire. Chi-square test data analysis found a significant relationship between support couple’s with a exclusive breastfeeding, with a p-value = 0,017 meaning p-value <0,05. Based on the results of the study the researchers suggested that the puskesmas and health workers expand the targets of health promotion related to exclusive breastfeeding involving the husband as the target